Health Communication Strategies to Prevent for the Chikungunya, Dengue and Zika - Denisse Isabel Suaste Pazmiño; Arianna Jael González Vargas; Karina Michelle Tricerri Moya (Medisur)
Health communication has become one of the key points for disease prevention and one of the fundamental axes of integrated health. The Latin America tropical areas have the highest incidence and prevalence of dengue, chikungunya and zika, which require greater health intervention. Governmental and non-governmental entities have worked on participatory communication strategies, providing knowledge and practical tools to the populations at greatest risk to act effectively in prevention, which allows them to react effectively to a possible contagion. The objective of this research was to describe the health communication strategies used for the prevention of arboviruses in Latin America. The analysis carried out showed the need to define more precisely the health communication problems according to the type of zoonotic disease and the region where they develop. Integrated participatory actions constitute effective strategies to improve health communication, which encourages the creation of planned guidelines adapted to each risk area to reduce the probability of outbreaks of this type of zoonotic diseases.